Removal of Acrylamida and Caffein in Gayo Arabica Coffe Beans by Vacum Roasting - Aja, C. Cut; Sami, M.; Saifuddin, S.; Nahar, N. (Devotion : Journal of Research and Community Service, 2023)
The conventional process of coffee roasting at high temperatures above 120oC, in addition to having high caffeine levels and reducing nutrients from coffee, will also cause the formation of acrylamide compounds causing cancer in humans. The coffee used was gayo arabica coffee (Green Bean). This study aims to produce healthy, acrylamide-free and low-caffeine coffee using a vacuum roaster. The coffee was roasted using a vacuum oven at a pressure of 0.1 bar (0.102 kgf/cm2) and at a temperature of 120, 140, and 160ºC with time variations ranging from 30, 60 and 90 minutes to obtain acrylamide-free and lower caffeine coffee. Gayo arabica coffee had acrylamide content of 0.48 mg/kg and Ijen robusta coffee of 0.659 mg/kgwhile the caffeine was 1406.87 ppm for Gayo arabica coffee and 3184.80ppm for Ijen robusta coffee. The acrylamide test was carried out using the high-performance liquid chromatography (HPLC) method at a wavelength of 202 nm, while the caffeine test was carried out using the UV-Vis Spectrophotometry method at a wavelength of 275 nm. The resulted coffee is considered safe for consumption because does not contain acrylamide and has lower caffeine content.